Effect of Red Onion (Allium cepa var ascalonicum) Skin Ethanolic Extract on the Motility and the Adhesion Index of Pseudomonas aeruginosa and Macrophage Phagocytosis Index - Irma Prasety Ayu Nugraheni; Derana Widyastika; Sofia Maulida; Heni Susilowati; Alma Linggar Jonarta (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Red onion skin (Allium cepa var ascalonicum) contains various ingredients that may function as antibacterial agents against microorganisms, as well as anti-inflammatory and immunomodulator agents for host cells, such as macrophages. Pseudomonas aeruginosa found in the oral cavity is commensal bacteria that may turn into opportunistic pathogen by utilizing its virulence factors such as motility and adhesion to the host cell. The purpose of this study was to investigate the effect of red-onion-skin ethanolic extract towards P. aeruginosa ATCC 9027 on the motility and adhesion ability, furthermore, to know its effect on the macrophage phagocytosis. The research was conducted into three parts of experiment using red-onion-skin ethanolic extract. Extract-induced bacterial motility test was carried out on semi-solid media, stained using 0.1% crystal violet, then the radial length of the bacterial movement was measured. The bacterial adhesion index to buccal cells was calculated after incubated for two hours and stained with Gram stain. Phagocytic activity of the host cells on P. aeruginosa was done by exposing the extract to the mouse peritoneal macrophages, then the phagocytosed bacteria were counted after Giemsa staining. Statistical test results from the three experiments showed significant differences between the test groups compared to the control groups (p <0.05). It was concluded that the red onion-skin ethanolic extract not only affects P. aeruginosa by reducing swarming motility and preventing bacterial adhesion to buccal epithelial cells, but also induces the host cells by increasing the ability of macrophage phagocytosis to these bacteria.